A cross-sectional observational study of the vertical distance between incisive papilla and incisal edge of maxillary central incisors among UPCD students - Bautista, Maria Joan A.
In complete denture prosthodontics, to restore the lost esthetics and function, the position of the denture teeth should be as close as possible to the natural dentition. The establishment of the incisal level is arbitrary and there is no definite guide. The study aims to measure the vertical distance between the incisive papilla and the incisal edge of the maxillary central incisors of UPCD students as well as to determine if there is a significant difference between males and females. The vertical distance was measured on casts of 51 participants (10 males and 41 females). T-test was utilized as the statistical method to determine if the measurements are significantly different (α=0.05). Results have shown that there is no significant difference between males and females. In addition, results have revealed that significant difference between the values obtained in this study and the study by Guldag et al. Conclusion of the study is: the mean vertical distance between the incisal edge of the maxillary central incisors and incisive papilla on the stone casts was 5,4147 ± 1.18424.